The Role of Virtual Social Interaction in Driving Adolescent Cognitive Development Based on Piaget's Theory - Mahadi, Rahmad; Zahra, Latifatuz; Mananna, M. Albab; Wigati, Indah; Yanti, Fitri Ovi (Al'ulum Jurnal Pendidikan Islam, 2026)
The purpose of the current research is to examine the extent to which social media and online games support Piaget’s notion of adolescents’ ability to think abstractly, reason in a structured way, and develop metacognition. The study relies on a qualitative descriptive method based on the most recent literature from the last five years. The study concluded that social interaction in virtual environments is a space where higher-order thinking, self-reflective thinking, and the ability to think hypothetically and deductively are developed. The ability to think formally and to reason is enhanced through social media and online games, where players must collaborate and engage in discussions. Consequently, what Piaget viewed as the symbiotic relationships between social interaction and knowledge construction should now include the emergence of new digital socialization technologies. Educational practitioners and parents are encouraged to guide the purposeful use of virtual socializations to foster adolescents’ cognitive development.